2018
DOI: 10.1007/s12011-018-1282-5
|View full text |Cite
|
Sign up to set email alerts
|

Hair Trace Elements in Overweight and Obese Adults in Association with Metabolic Parameters

Abstract: The objective of the present study was to investigate the level of toxic and essential trace elements in hair of adult overweight and obese persons as well as its association with metabolic parameters. Hair trace element levels were assessed using inductively coupled plasma mass-spectrometry in 112 overweight and obese patients and 106 lean controls. Serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG), glucose, uric acid (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 62 publications
2
16
0
1
Order By: Relevance
“…However, we measured V in MS and AF and in several other studies V was assessed in the urine. The results obtained in this study may be related to the fact that macrosomia is strongly associated with pre-pregnancy overweight and obesity, and in obese people, low concentrations of V and Co have been reported [39,40,41]. Therefore, obese women with low levels of V and Co may be at high risk of fetal macrosomia.…”
Section: Discussionsupporting
confidence: 54%
“…However, we measured V in MS and AF and in several other studies V was assessed in the urine. The results obtained in this study may be related to the fact that macrosomia is strongly associated with pre-pregnancy overweight and obesity, and in obese people, low concentrations of V and Co have been reported [39,40,41]. Therefore, obese women with low levels of V and Co may be at high risk of fetal macrosomia.…”
Section: Discussionsupporting
confidence: 54%
“…Skalnaya et al presented that hair from overweight and obese people had significantly lower Mg levels, which may be associated with hypomagnesemia and obesity [ 38 ] (LOE IV, LOE II). The purpose of the study was to investigate the levels of toxic and essential trace elements in the hair of adult overweight and obese people, as well as their association with metabolic parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of the study was to investigate the levels of toxic and essential trace elements in the hair of adult overweight and obese people, as well as their association with metabolic parameters. The level of minerals was evaluated and the correlation between body mass and the level of magnesium was found to be the strongest [ 38 ]. The aim of the next study was to compare the effect of endurance and endurance–strength training on mineral levels in 44 women with abdominal obesity; it was suggested that endurance–strength training decreased hair Mg levels [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…A small bend in 1100-1000 sm -1 is caused by ions PO 4 3- [15]. We can conclude that the dominant anions in hair ash residue are (in decreasing order): SO 4 2-> CO 3 2-> PO 4 3-. XRD showed (Fig.…”
Section: -2mentioning
confidence: 71%